Binocular Triplopia Due to Decompensated Congenital Superior Oblique Paresis in A Patient with Marfan Syndrome; A Case Report and Review of Literature. Issue 1 (2nd January 2021) - Arcot Sadagopan, Karthikeyan; Hui, Gong; Radke, Nishant; Lin, Timothy P. H.; Lam, Dennis
ABSTRACT: Binocular triplopia is a rare symptom and usually has a corneal or lenticular origin. Uniocular diplopia arising from ectopia lentis is quite common in Marfan syndrome. A visual phenomenon related to binocular triplopia due to strabismus was first reported in 1943 by Burian. Both monocular diplopia and binocular triplopia have been reported in concomitant strabismus. Strabismus is also common in Marfan syndrome but congenital superior oblique paresis has never been reported before. We report herein a rare case of binocular triplopia in a patient with Marfan syndrome arising from decompensation of his coexistent congenital superior oblique paresis triggered by his uniocular diplopia. This is the first report of congenital superior oblique paresis in a patient with Marfan syndrome. Though it is unlikely to have any etiological implications and is likely to be a mere coincidental simultaneous occurrence, it had a confounding effect on the clinical interpretation of the signs and symptoms posing an interesting diagnostic and management dilemma. Our case report emphasizes the necessity for careful evaluation of any patient with symptoms of triplopia. We further review and summarize all the causes of binocular triplopia published in English literature and propose an approach to its evaluation and management.